La perception de l’intervention par le Client et l’Impact Thérapeutique - Bouchard, Marc-André; Lecomte, Conrad; Charbonneau, Luce (Canadian Journal of Counselling and Psychotherapy, 2011)
The present article reports on the development of a two scale measure of client perceived therapist skills for social skills training. The first, with 9 items, is the Perceived Problem Specification Skills (CPPS); the other, with 30 items, is the Client Perceived Social Skills Training scale (CPSS), which embraces various SST skills (modelling, feedback, roleplaying, etc.). Both scales show high levels of internal consistency. Although client perceptions do not correlate with ratings of therapist behaviours in actual sessions, as predicted the CPSS scale is shown to relate, albeit marginally, with individual measures of therapy outcome. These results are discussed in terms of the issue of limited inter-source agreement. Further, the necessity to better evaluate the client's perceptual reality is stressed.